Efeito de diferentes periodizações do treinamento aeróbio sobre o limiar anaeróbio ventilatório - Sauer, Deborah (2013)
There are in the literature a large number of studies evaluating the effects of training on the ventilatory anaerobic threshold (VAT) of individuals with different physiological profiles. However, none of them investigated a possible influence of the application of overload in exercise intensity on this parameter, in a periodized way. The main objective was to study the effect of aerobic training, with progression of intensity, in a way undulatory, growing and stepped on the VAT and VO2peak. Secondarily to evaluate the effects of training on ventilatory efficiency and heart rate (HR) associated with VAT. It was hypothesized that the VAT increased would be enhanced in the group with a model of periodization growing, and that the absolute increase of VAT would exceed the peak VO2 increase of the three groups. Were recruited 48 healthy, active men and randomly assigned to three groups: growing (GROW n = 15), undulatory (UND n = 18) and stepped (STEP n = 15). The groups were subjected to 13 weeks of walking and / or running, three times a week for 30 minutes. The initial intensity of 65% HRmax was increased to 90% of HRmax, for the three groups, but the structure of this progression occurred differently for each group. The three groups increased VO2VAT (UND: 29,1 ± 4,3 vs. 32,2 ± 4,1; GROW: 29,9 ± 4,6 vs. 34 ± 5,7; STEP: 32,8 ± 4,6 vs. 35,7 ± 4,9 ml.kg-1.min-1. p <0.05), VO2peak (UND: 52,6 ± 6,8 vs. 57,8 ± 10,4; GROW: 52,9 ± 10,2 vs. 57,7 ± 10,4; STEP: 54,2 ± 8,1 vs. 61,5 ± 8,7. ml.kg-1.min-1 p <0.05), and ventilatory efficiency, but no were differences between them. The absolute magnitude of the increase in the VAT and VO2peak, was proportional on UND and GROW groups, but the increase of VO2peak on STEP group was superior to that found in VO2VAT. There were no changes in %VO2VAT and FC at VAT. It was concluded that 1) the progression models of intensity stepped and undulatory showed the same efficacy as the model growing in increasing the VAT and VO2peak; 2) the absolute increase of VAT was not superior to that found in VO2peak on three groups; 3) there was a maintenance of measure of HR at VAT after training; 4) the increase in ventilatory efficiency in the conditions of the present study was not affected by the total training load.